Effects of Colloquial Language on the Writing Skills of Grade 11 Students - Briones, Sherry H.; Abundo, Leizel V.; Quiñones, Pauline S.; Regilme, Krizzia Mae D.; Catalan Jr., Joseph C.; Cañeza, Donna Claire B.; Ocampo, Darrel M. (Journal of English Education Forum (JEEF), 2024)
This study aimed to investigate the effects of colloquial language on the English writing skills of Grade-11 students. It evaluates the prevalence of colloquial language usage, encompassing contractions, abbreviations, and sentence structures. Concurrently, it conducts a comprehensive assessment of students' writing skills, specifically emphasizing grammar, spelling, and coherence. The research methodology employed a quantitative approach, implementing a descriptive-correlational design. A rigorously selected random sample of 83 Grade 11 students from San Juan National High School forms the basis of this study. Data collection procedures include the utilization of a validated researcher-designed survey questionnaire coupled with the systematic analysis of written essays through the application of analytical rubrics. Empirical findings stemming from this investigation underscore the commendable writing proficiency of the students, with 30% demonstrating proficiency in grammar, 80% in spelling, and 28% in coherence. The p>0.05 indicates that there is no significant correlation between colloquial language usage and the level of writing skills of the participants. These findings offer valuable insights into the limited impact of colloquial language on the development of writing skills, irrespective of prevailing linguistic variations within society. Consequently, educators are encouraged to consider the judicious integration of opportunities for students to engage with colloquial language within contextually appropriate boundaries.